2017
DOI: 10.1002/ird.2178
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Groundwater Service Markets in a Palm Grove in the Algerian Sahara

Abstract: Groundwater service markets are important and dynamic institutions that provide water to a wide range of farmers in many regions. However, these institutions represent arenas of complex and often antagonistic relations, which determine which farmers gain access to water and how. This study analyses the emergence and functioning of groundwater service markets from a historical perspective to advance the understanding of the role of social power games in shaping these institutions. The study was conducted in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Comparative research has also demonstrated how cultural differences in norms of justice and fairness shape acceptability of water markets [6], how legal conditions affect their suitability [29] and how individuals and communities have balanced benefits and risks of participating in markets [25]. These trends have coincided with efforts to broaden performance measurement beyond important economic studies to account for a range of impacts and outcomes related to justice, sustainability, and health.…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative research has also demonstrated how cultural differences in norms of justice and fairness shape acceptability of water markets [6], how legal conditions affect their suitability [29] and how individuals and communities have balanced benefits and risks of participating in markets [25]. These trends have coincided with efforts to broaden performance measurement beyond important economic studies to account for a range of impacts and outcomes related to justice, sustainability, and health.…”
Section: Measurementmentioning
confidence: 99%
“…For example, an international team from Kathmandu conducted a rare repeat study of water vending to develop a system-wide picture amidst changes in urbanization, water availability, and infrastructure coverage [10]. Farmer surveys of market participants from Australia to Algeria have generated insight about irrigator behavior in the face of shifting incentives created by markets, including the determinants of water sales, farm exit, and mental health impacts [9,25]. Experimental and quasi-experimental research designs have enabled causal inferences about the effects of different policy levers and technologies, such as in West Bengal, where farmers who owned electric pumps sold more water to smallholders than farmers who owned diesel pumps due to cost differences across technologies [26].…”
Section: Measurementmentioning
confidence: 99%
“…Two papers deal with groundwater governance issues in Algeria: Hamamouche et al . () analyse the historical conditions of emergence of groundwater service markets; Amichi et al . () demonstrate how individual farmers' initiatives and public investment interact to participate in the pioneering dynamics of an irrigated territory based on groundwater exploitation.…”
mentioning
confidence: 99%